Colorectal cancer‐initiating cells caught in the act - Dieter, Sebastian M.; Glimm, Hanno; Ball, Claudia R. (EMBO molecular medicine, 2017)
Our increased awareness of the clonal organization of many hematological and solid cancers has dramatically changed our view on the design of novel therapeutic approaches for cancer. Tumor‐initiating cells (TIC) (a.k.a. cancer stem cells) are on the apex in this hierarchy and can self‐renew and differentiate, thereby continuously fueling tumor growth and metastasis formation. This process was previously thought to be unidirectional. Self‐renewing TIC therefore represent highly attractive targets for therapeutic intervention.